Engineering and Modulating Functional Cyanobacterial CO2-Fixing Organelles - Fang, Yi; Huang, Fang; Faulkner, Matthew; Jiang, Qiuyao; Dykes, Gregory F.; Yang, Mengru; Liu, Lu-Ning (Frontiers in Plant Science, 2018)
Bacterial microcompartments (BMCs) are proteinaceous organelles widespread among bacterial phyla and provide a means for compartmentalizing specific metabolic pathways. They sequester catalytic enzymes from the cytoplasm, using an icosahedral proteinaceous shell with selective permeability to metabolic molecules and substrates, to enhance metabolic efficiency. Carboxysomes were the first BMCs discovered and their unprecedented capacity of CO2 fixation allows cyanobacteria to make a significant contribution to global carbon fixation. There is an increasing interest in utilizing synthetic biology to construct synthetic carboxysomes in new hosts, i.e. higher plants, to enhance carbon fixation and productivity. Here, we report the construction of a synthetic operon of β-carboxysomes from the cyanobacterium Synechococcus elongatus PCC7942 to generate functional β-carboxysome structures in Escherichia coli. The protein expression, structure, assembly, and activity of synthetic β-carboxysomes were characterized in depth using confocal, electron and atomic force microscopy, proteomics, immunoblot analysis, and enzymatic assays. Furthermore, we examined the in vivo interchangeability of β-carboxysome building blocks with other BMC components. To our knowledge, this is the first production of functional β-carboxysomes in heterologous organisms. It provides important information for the engineering of fully functional carboxysomes and CO2-fixing modules in higher plants. The study strengthens our synthetic biology toolbox for generating BMC-based organelles with tunable activities and new scaffolding biomaterials for metabolic improvement and molecule delivery.